Dakwah Peningkatan Pemahaman Agama Melalui Kegiatan Traumatic Healing - Gina Santia (Jurnal Riset Komunikasi Penyiaran Islam, 2021)
Abstract. The tragedy of a natural disaster that occurred in Cihanjuang Village, Cimanggung District, Sumedang Regency, West Java. Leaving a sense of trauma for local residents, especially children. This condition has motivated the Indonesian Islamic Student Organization (PII) in Bandung to organize traumatic healing activities for victims of the Cimanggung natural disaster. Apart from being an effort to restore the psychological condition of children after the disaster, traumatic healing activities are also activities that have the value of Islamic da'wah. Considering the condition of children victims of the Cimanggung natural disaster in terms of their religious understanding which is still very minimal. In traumatic healing activities, the counselors provide an understanding of Islam to children, through the playing thrapy method and spiritual therapy (spiritual emotional freedom technique). This study aims to measure the level of religious understanding of children who are victims of natural disasters after participating in traumatic healing activities. The research method used is quantitative method and the statistical method used is statistics with a Likert scale. The data analysis techniques used are validity test, reliability test, correlation test, simple linear regression analysis, hypothesis testing, and coefficient of determination test. The findings in this study are in the form of the value of the relationship between the independent variable (X), namely traumatic healing activities, to the dependent variable (Y) or religious understanding of 44.2%. This means that traumatic healing activities have the effect of increasing religious understanding for children who are victims of the Cimanggung natural disaster who participate in traumatic healing activities. While the remaining 55.8% was influenced by other factors outside of traumatic healing which were not studied. Abstrak. Tragedi bencana alam yang terjadi di Desa Cihanjuang, kecamatan Cimanggung, Kabupaten Sumedang, Jawa Barat. Menyisakan rasa trauma bagi warga sekitar, khususnya anak-anak. Kondisi tersebut, membuat organisasi Pelajar Islam Indonesia (PII) Kota Bandung tergerak untuk mengadakan kegiatan traumatic healing terhadap korban bencana alam Cimanggung. Selain sebagai upaya memulihkan kembali kondisi psikologis anak-anak pasca bencana, kegiatan traumatic healing juga menjadi kegiatan yang bernilai dakwah Islam. Mengingat kondisi anak-anak korban bencana alam Cimanggung dari segi pemahaman agamanya yang masih sangat minim. Dalam kegiatan traumatic healing, para konselor memberi pemahaman agama Islam terhadap anak-anak, melalui metode playing thrapy dan terapi spiritual (spiritual emotional freedem technique). Penelitian ini bertujuan untuk mengukur besaran tingkat pemahaman agama anak-anak korban bencana alam setelah mengikuti kegiatan traumatic healing. Metode penelitian yang dilakukan adalah metode kuantitatif dan metode statistik yang digunakan adalah statistik dengan skala likert. Adapun teknik analisis data yang digunakan berupa uji validitas, uji reabilitas, uji korelasi, analisis regresi linear sederhana, uji hipotesis, dan uji koefisien determinasi. Temuan dalam penelitiaan ini berupa nilai besaran hubunga variabel independent (X) yakni kegiatan traumatic healing, terhadap variabel dependen (Y) atau pemahaman agama sebesar 44,2%. Artinya, kegiatan traumatic healing memberikan pengaruh peningkatan pemahaman agama terhadap anak-anak korban bencana alam Cimanggung yang mengikuti kegiatan traumatic healing. Sedangkan sisanya sebesar 55,8% dipengaruhi oleh faktor lain diluar traumatic healing yang tidak diteliti.